INTRICATELY DISLOCATED CARBONACEOUS ROCKS ON THE WESTERN SLOPE OF THE SOUTHERN URALS - Kovalev S.G. (My University, 2004)
The data indicate that the formation of intricately deformed carbonaceous rocks in tectonic zones is related to the transformation of primary sedimentary rocks by abyssal intratelluric fluids that penetrate upper crustal layers during faulting at early riftogenic stages or tectonomagmatic activation of the region. The mantle fluid is composed of reduced hydrogen or nitrogen and carbon [10]. If the fluid penetration into the upper crustal layers predates magmatism and the redox environments are inversed, it is oxidized, with the formation of carbon (CH4 + CO2 = 2C + H2O), which imparts a black color to terrigenous rocks. The influx of mantle-derived elements at this stage is responsible for the atypical geochemical specialization of terrigenous rocks. These processes result in the formation of intricately dislocated black shales (with anomalous PGE contents and peculiar mineralization) resembling typical sedimentary formations or rocks altered at premetamorphic stages, and their metamorphism can be defined as a syngenetic hydrothermal process.